Analisis Pengaruh Brand Equity Berbasis Konsumen (CBBE) terhadap Purchase Intention Smartphone di Surabaya (PLS-SEM) - Sunarjanto, Nekhasius Agus; Sumayouw, Vicky Giovanni (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2026)
The current generation is a generation that uses high-level technology and also the use of smartphones continues to increase sharply, of course this cannot be separated from the role of brand equity in these smartphone products. This research aims to analyze the role of brand awareness, brand associations, perceived quality, brand loyalty, brand trust in driving purchase intentions in this digital era. This research uses a research design with a quantitative approach. Data was collected through documentation and distributing questionnaires online. This study used a sample of 202 respondents. This study proposed five hypotheses, and two of them were rejected: the influence of brand awareness and brand association on purchase intention was insignificant. Meanwhile, perceived quality, brand loyalty, and brand trust significantly influenced purchase intention. Nevertheless, this study yielded an R2 of 0.618, or 61.8%, indicating that brand awareness, brand association, perceived quality, brand loyalty, and brand trust significantly influenced purchase intention. The benefits of this research are expected to encourage smartphone companies to prioritize strategies that strengthen product quality perceptions, build brand loyalty, and increase consumer trust, as these three dimensions have been shown to significantly influence purchase intention, rather than simply increasing brand awareness and association.